2000
DOI: 10.1080/003655200750023769
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal in Vitro Permeability in the Intestinal Tract of the Pig, the Rat, and Man: Species- and Region-Related Differences

Abstract: The results showed differences between intestinal regions and between species. Permeability data from the pig correlated fairly well with those of man, whereas the rat differed, making it difficult to extrapolate from the rat to man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…We also assessed for markers that are equally expressed throughout the intestinal tract and found that GATA6, ECAD, and LGR5 were similarly expressed in both groups of organoids [44,45]. The finding that the basal P app of 0.41-0.44 × 10 −7 cm/s of HCOs ( Figure 3B) compares favorably to previous reports using Caco-2 monolayers (0.2-0.5 × 10 −7 cm/s) and human colon (0.1-0.2 × 10 −7 cm/s) recording in Ussing chambers [27,30,33,46]. The 2-2.5 fold decrease in intestinal permeability in colonic epithelium favorably reflects previously published data that show that there is 2-4 fold decrease in permeability in both rat and human explants of small and large intestinal cells ( Figure 2B, Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…We also assessed for markers that are equally expressed throughout the intestinal tract and found that GATA6, ECAD, and LGR5 were similarly expressed in both groups of organoids [44,45]. The finding that the basal P app of 0.41-0.44 × 10 −7 cm/s of HCOs ( Figure 3B) compares favorably to previous reports using Caco-2 monolayers (0.2-0.5 × 10 −7 cm/s) and human colon (0.1-0.2 × 10 −7 cm/s) recording in Ussing chambers [27,30,33,46]. The 2-2.5 fold decrease in intestinal permeability in colonic epithelium favorably reflects previously published data that show that there is 2-4 fold decrease in permeability in both rat and human explants of small and large intestinal cells ( Figure 2B, Table 1).…”
Section: Discussionsupporting
confidence: 82%
“…Results are in good agreement with those reported for the pig by others [31][33], when also including tissue-specific differences between ileum and colon. Overall, our results suggest that subtle but important changes are observed in both ileum and colon in the cases of unprotected anastomosis.…”
Section: Discussionsupporting
confidence: 91%
“…We will focus on the data obtained in humans, laboratory animals, poultry and pigs, as this latter species can be regarded as a good model for man [16,17]. …”
Section: Introductionmentioning
confidence: 99%